Experience of breastfeeding mother’s in treating cracked nipples - Yani Marlina; Irisanna Tambunan (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Nipple trauma is one of the most common problems experienced by mothers during the early breastfeeding period and is a major cause of discomfort and pain during breastfeeding. This condition not only affects physical well-being but also influences maternal emotional status, self-confidence, and motivation to continue breastfeeding. If not managed appropriately, nipple trauma may lead to early cessation of breastfeeding and hinder the achievement of exclusive breastfeeding programs. Although various treatment methods have been recommended, mothers’ choices and the effectiveness of these methods are strongly influenced by their experiences, perceptions, and the support they receive. Purpose: To explore in depth breastfeeding mothers’ experiences in managing nipple trauma, including their perceptions of its causes, selected care strategies, barriers encountered during the care process, and the role of social and professional support. Method: A qualitative study with a descriptive phenomenological approach was conducted. Five breastfeeding mothers who experienced nipple trauma within the past year were recruited using purposive sampling. Data were collected through semi-structured in-depth interviews conducted between September and November 2025. Data analysis was performed using Colaizzi’s method through systematic and detailed stages. Results: Mothers perceived nipple trauma as a condition that caused both physical pain and emotional burden. The main contributing factors included improper latch-on technique, maternal fatigue, and changes in nipple skin condition. Mothers applied various care methods; however, they frequently faced limited and inconsistent information. Support from family members and health professionals played a crucial role in maintaining breastfeeding continuity. Conclusion: Mothers’ experiences in managing nipple trauma represent a complex process influenced by the interaction of physical, psychological, and social factors. Practical, evidence-based, and easily accessible breastfeeding education, along with early professional support, is essential to prevent nipple trauma and support the success of exclusive breastfeeding.